Flow and mixing by small intestine villi. Issue 6 (10th June 2015) - Lim, Y. F.; de Loubens, C.; Love, R. J.; Lentle, R. G.; Janssen, P. W. M.
<x xml:space="preserve">Abstract</x> Villous movements augmented radial mass transfers and mixing.